Design, synthesis, and biological evaluation of triazole-pyrimidine-methylbenzonitrile derivatives as dual A2A/A2B adenosine receptor antagonists - Zhi Li; Lijuan Kou; Xinzhen Fu; Zeping Xie; Maolei Xu; Lin Guo; Tiantian Lin; Shizhou Gong; Shumin Zhang; Ming Liu (Journal of Enzyme Inhibition and Medicinal Chemistry)
A series of novel dual A2A/A2B AR antagonists based on the triazole-pyrimidine-methylbenzonitrile core were designed and synthesised. The A2A AR antagonist cAMP functional assay results were encouraging for most target compounds containing quinoline or its open-ring bioisosteres. In addition, compound 7i displayed better inhibitory activity on A2B AR (IC50 14.12 nM) and higher potency in IL-2 production than AB928. Moreover, molecular docking studies were carried out to explain the rationality of molecular design and the activity of compound 7i. Further studies on 7f and 7i revealed good liver microsomes stabilities and acceptable in vivo PK profiles. This study provides insight into the future development of dual A2A/A2B AR antagonists for cancer immunotherapy.